2011
DOI: 10.1038/npp.2011.20
|View full text |Cite|
|
Sign up to set email alerts
|

Perturbation of the Glutamate–Glutamine System in Alcohol Dependence and Remission

Abstract: As acute ethanol exposure inhibits N-methyl-D-aspartate glutamate (Glu) receptors, sudden withdrawal from chronic alcohol use may lead to an increased activation of these receptors with excitotoxic effects. In the longer term, brain levels of Glu and its metabolites, such as glutamine (Gln), are likely to be chronically altered by alcohol, possibly providing a measure of overall abnormal Glu-Gln cycling. However, few studies have assessed concentrations of these metabolites in clinical populations of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 34 publications
4
57
1
Order By: Relevance
“…The unchanged tissue concentration of glutamine in NAc suggests differential adaptations in mPFC and NAc following severe withdrawal. However, our current finding of decreased glutamate and increased glutamine content is consistent with a previous study conducted on human volunteers, through proton magnetic resonance spectroscopy, with alcohol dependence (Thoma et al, 2011). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The unchanged tissue concentration of glutamine in NAc suggests differential adaptations in mPFC and NAc following severe withdrawal. However, our current finding of decreased glutamate and increased glutamine content is consistent with a previous study conducted on human volunteers, through proton magnetic resonance spectroscopy, with alcohol dependence (Thoma et al, 2011). …”
Section: Discussionsupporting
confidence: 93%
“…The effects of imported glutamate within astrocytes include: formation of glutamine by glutamine synthetase (GS) enzyme, exchanging for cystine to the extracellular space through xCT, and subsequent formation of glutathione. The formed glutamine within astrocytes is further used up by neurons, and this recycle process is termed the glutamate-glutamine cycle (Thoma et al, 2011). Thus, GLT-1, xCT and GLAST play key roles in regulating extracellular glutamate concentration in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests enhanced glutamatergic signaling in these areas that might drive continued excessive drinking or relapse (e.g., Gass & Olive, 2008). It is possible that these increases in glutamate may reflect withdrawal-induced excitability or time in remission, as other studies using magnetic resonance spectroscopy revealed reduced levels of glutamate in anterior cingulate of alcohol-dependent subjects (Mon, Durazzo, & Meyerhoff, 2012;Thoma et al, 2011), a finding consistent with the data from animal studies suggesting that alcohol-induced alterations in extracellular glutamate may vary as a function of alcohol withdrawal (Ding et al, 2012b).…”
Section: Glutamate Release / Uptakementioning
confidence: 94%
“…Acute alcohol exposure inhibits glutamate receptors, e.g. the NMDA-R, while chronic alcohol exposure reduces brain levels of glutamate (Thoma et al, 2011). GABA has been implicated in alcohol induced functional changes in the brain both in rodents (Feller et al, 1988) and in humans (Maccioni & Colombo, 2009).…”
Section: Methodsmentioning
confidence: 99%